(untitled) (Journal of actual problems of jurisprudence, 2018)
In the scientific article the author in details considers qualification problems on the objective part of the crimes encroaching on ecological safety through a prism of the existing and projected criminal legislation of Republic of Kazakhstan. The author made attempt to add objectively some structures of the crimes encroaching on ecological safety in the new edition: articles 277,278,279,294 Criminal Code of Republic of Kazakhstan and articles 329,330,331,348 Criminal Code of Republic of Kazakhstan (project). The author accurately defined results of research having proved them by program documents of Republic of Kazakhstan , the points of view of various domestic and foreign scientists, foreign practice of application of the criminal legislation and empirical data. Keywords: ecology, ecological safety, the objective part, the crimes encroaching on ecological safety, qualification of crimes.